News Media Performance Evaluated by National Audiences: How Media Environments and User Preferences Matter - Steppat, Desiree (2020)
Media fragmentation and polarization have contributed to blurring the lines between professional and non-professional journalism. Internationally, more fragmented-polarized media environments are often associated with the emergence of non-professional news providers, the weakening of journalistic standards, and the segmentation of audiences along ideological leanings. Furthermore, these environments are home to partisan and alternative news media outlets, some of which try to actively undermine the credibility of traditional mainstream media in their reporting. By following an audience-centric approach, this study investigates the consequences of more fragmented-polarized media environments and consumption habits on users’ perceptions of news media performance. We use online-survey data from five countries that differ in the extent of fragmentation and polarization in the media environment (CH = 1,859, DK = 2,667, IT = 2,121, PL = 2,536, US = 3,493). We find that perceptions of high news media performance are more likely to be expressed by citizens from less fragmented-polarized media environments. Positive perceptions of news media performance are also stronger among users of traditional media, and those who inform themselves in a more attitude-congruent manner. By contrast, citizens from more fragmented-polarized media environments and users of alternative news media tend to express less satisfaction with news media performance. Based on these results, we argue that perceptions of news media performance among news users are shaped by their individual media choices as well as by the composition of the news media environments that surrounds them.